RELIGION IN RELATION TO GLOBALIZATION PROCESSES (Религиски дијалог и соработка, 2024)
Rational the relationship of globalization with social institutions, focusing on the termof globalization of modernity, religion and religious phenomena are of unavoidable interest. Interestin religious phenomena is on the rise, and globalization as such is multifaceted. Never beforehave there been so many nonreligious people in human history, as well as never before in humanhistory has there been so much religious population on the planet. Globalization and religion arelinked through the following aspects: religious diversity is on the rise, the difference at the levelof organization is increasing, as well as that the subjective religiosity is being strengthened. Thementioned aspects are theoretically based on the globalization of modernity, which implies theaspects of the diffusion of processes, as well as the dynamics, which are typically modern in natureand extend to the world level even in their influence. As the most typical modern processes anddynamics are: speed, widespread and continuous process of transformation of society, structuraldifference, detraditionalization, and individualization. Undoubtedly, the enumerated processes ofmodern globalization have their impact on religion. The aim of this article is to theoretically elaboratethe indicated aspects through a review of the relevant literature. The theoretical frameworkwill be used as a concept or further empirical research on the connection between religion andglobalization.